1992
DOI: 10.3109/10715769209079515
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Kb: An Oxidative Stress-Responsive Transcription Factor of Eukaryotic Cells (A Review)

Abstract: NF-kappa B is a multiprotein complex that can activate a great variety of genes involved in early defence reactions of higher organisms. In nonstimulated cells, NF-kappa B resides in the cytoplasm in an inactive complex with the inhibitor I kappa B. Pathogenic stimuli cause release of I kappa B and allow NF-kappa B to enter the nucleus, bind to DNA control elements and, thereby, induce the synthesis of mRNA. A puzzling feature of NF-kappa B is that its activation is triggered by a great variety of agents. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
706
1
11

Year Published

1995
1995
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,351 publications
(741 citation statements)
references
References 51 publications
23
706
1
11
Order By: Relevance
“…It is likely that this induction of antioxidant enzymes represents a stress response to the hypoxia since Das et al have shown that Mn SOD and catalase are two of a number of stress-related genes up-regulated in cardiac biopsy tissue following repeated ischaemia [38]. Whether the anti-apoptotic effect of hypoxia relates to the induction of other stress-related proteins or changes in poly-ADP-ribose transferase activity and hence ATP levels [39,40], lipid oxidation [41], regulation of NF~B activation [42], or some alternative mechanism, requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that this induction of antioxidant enzymes represents a stress response to the hypoxia since Das et al have shown that Mn SOD and catalase are two of a number of stress-related genes up-regulated in cardiac biopsy tissue following repeated ischaemia [38]. Whether the anti-apoptotic effect of hypoxia relates to the induction of other stress-related proteins or changes in poly-ADP-ribose transferase activity and hence ATP levels [39,40], lipid oxidation [41], regulation of NF~B activation [42], or some alternative mechanism, requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…CHOP-regulated genes relevant for apoptosis regulation have not yet been identi®ed but may include pro-apoptotic molecules such as the Bcl-2 family member Bax, a known trigger of cytochrome c release on mitochondria (Rosse et al, 1998). On the other hand, it is known that activation of the transcription factor NF-kB via the EOR involves reactive oxygen species (ROS) which are produced from the oxidizing environment of the ER lumen and the action of cytochrome p450 on the ER membrane (Pahl and Baeuerle, 1997;Schreck et al, 1992). ROS can mount an oxidative stress that damages membranes, including those of mitochondria (Kowaltowski and Vercesi, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…PCBs also can produce oxidative DMA damage, in the form of 8-hydroxydeoxyguanosine (Oakley et al 1996). We have observed that PCBs can activate NF-κB, which may be activated by oxidative stress (Li and Karin 1999;Schreck et al 1992;vandenBerg et al 2001). We examined two PCBs: 3,3′ 4,4′-tetrachlorobiphenyl (PCB-77), an Ah receptor agonist; and 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB-153), a CAR activator.…”
Section: Introductionmentioning
confidence: 99%